Perceived Control and Hedonic Tone Dynamics During Performance in Elite Shooters. Issue 3 (2nd July 2016) - Robazza, Claudio; Bertollo, Maurizio; Filho, Edson; Hanin, Yuri; Bortoli, Laura
Abstract : Purpose: The purpose of the study was to investigate the individuals' dynamics of perceived control and hedonic tone over time, with respect to the 4 performance states as conceptualized within the multiaction plan (MAP) model. We expected to find idiosyncratic and differentiated trends over time in the scores of perceived control and hedonic tone, typified by fluctuations among 2 optimal and 2 suboptimal types of processing during performance.Method: Ten elite-level shooters participated in the study. They were asked to identify the most relevant, idiosyncratic core component of their shooting action and perform 120 shots distanced 10 m from the target. Subjective accounts of perceived control and hedonic tone of the core component of action were assessed prior to and after each shot. We used a probabilistic approach to derive the 4 performance categories according to 2 × 2 interactions of perceived control and performance and hedonic tone and performance.Results: Logistic ordinal regression analysis enabled the identification of 4 idiosyncratic performance types for each athlete with respect to perceived control and hedonic tone intensity scores. Within- and between-individual differences in intensity bandwidth and probability levels were apparent across the 4 performance types. Changes among 4 types of processing were also observed during performance.Conclusion: Consistent with the MAP model conceptualization, the findings provided support for the different patterns of perceived control and hedonic tone intensity scores during performance. The results suggest applied arguments for using action- and emotion-centered strategies to help athletes in reaching and sustaining optimal performance states.